Immobilization of Bacillus sp. Strain Neni-8 in Dialysis Tubing Reduced Copper Toxicity to the Molybdenum Reduction Process (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
In ruminants, even trace amounts of molybdenum can be lethal. In areas with high pollution, molybdenum levels in soil and mine tailings can exceed 20,000 ppm. Bioremediation of molybdenum can be challenging when toxic copper is also present. This research presents a novel approach using dialysis tubing and the molybdenum-reducing activity of Bacillus sp. strain Neni-8 for molybdenum removal from aqueous solutions. Molybdenum blue (Mo-blue), produced during enzymatic reduction, is insoluble in dialysis tubing and this can be a twofold advantage as a method of removal and as a method to protect bacterial cells from heavy metal inhibition, especially copper. In this experiment, we assess the toxicity-shielding effect of dialysis tubing for molybdenum reduction to Mo-blue by this bacterium in the presence of copper. As the concentrations of copper were increased, both free and immobilized cells were strongly inhibited. Modelling using the dissociationone-phase exponential decay model gave an IC50 value for the immobilized form of 0.1107 mg/L (95% confidence interval from 0.073 to 0.217 while the IC50 value for the free cell system was 0.023 mg/L (95% C.I. from 0.019 to 0.028). Since the confidence interval for the IC50 values did not overlap, the immobilized system gave better protection from copper than the free cell system. Toxicity to free cells was higher than toxicity to cells trapped in dialysis tubes, suggesting that trapping Mo-reducing cells may be an effective strategy for the bioremediation of water or wastewater contaminated with multiple heavy metals.
Keywords: Bioremediation; Molybdenum; Molybdenum blue; Copper; Dialysis tubing